DINAMIKA PENGELOLAAN HUTAN DESA KENEGERIAN GUNUNG SAHILAN OLEH LEMBAGA PENGELOLA HUTAN DESA KENEGERIAN GUNUNG SAHILAN DALAM PERESPEKTIF KONFLIK - ", Hendriawan; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The dynamics of village forest management is an institutional problem that occurs in the village forest management institutions of the Gunung Sahilan village which is one of the factors causing the village forest management to be poorly managed, the benefits of the village forest to the community economy to be one of the problems that occur here. Local wisdom is a custom that is still held by the forest where forest management is given to the ninik mamak group, while ninik mamak does not have the competence in managing the forest, transparency of forest management to the community is one of the dynamics that occurs due to the inadequate communication between the manager, the village government and the community These factors cause the village forest to not be useful for the community.Keywords: dynamics, conflict, institutional.